Integrating ecosystem service trade-offs and rocky desertification into ecological security pattern construction in the Daning river basin of southwest China. (May 2022) - Gou, Mengmeng; Li, Le; Ouyang, Shuai; Shu, Chang; Xiao, Wenfa; Wang, Na; Hu, Jianwen; Liu, Changfu
Highlights: Ordered weighted averaging method was used to handle ecosystem service trade-offs. Ecological sources were selected based on the conservation efficiency. Proposed a resistance surface framework considering the characteristics of the karst. Ecological security patterns showed that large-scale farmland hampered connectivity. Abstract: The construction of ecological security patterns (ESPs) from the perspective of ecosystem services is vital in regional sustainability. However, previous approaches have often not considered the complex trade-offs between ecosystem services during the construction of ESPs. Taking the Daning river basin in karst areas of southwest China as our study area, we improve the current methodological framework to construct an ESP by integrating ecosystem service trade-offs, typical characteristics of the karst area, and circuit theory. The multi-criterion decision method of ordered weighted averaging was used to balance ecosystem service trade-offs and to determine the ecological sources with the optimum conservation efficiency. The resistance surface based on land use was modified by the nighttime light intensity and rocky desertification index. Circuit theory was then applied to identify corridors, pinch points and barriers. The results showed that the spatial patterns of the six ecosystem services (food provision, carbon sequestration, soil retention, water yield, habitat quality and ecological recreation) varied considerably within the study area. By comparing the conservation efficiencies, scenario 5 was selected as the optimal scenario, and the conservation efficiencies of six ecosystem services within the ecological sources were > 1 and were more balanced, illustrating the flexibility and feasibility of our method. The modified resistance surface comprehensively reflected the dual influence of human activity and rocky desertification on ecosystems. The ESP in the Daning river basin included 34 ecological sources, 66 key corridors, ecological corridors with an area of 957 km 2, and 100 pinch points and 36 barriers distributed on the corridors. The ecological sources mostly covered by forest land were mainly distributed in the north and east of the study area. The key and ecological corridors were densely located in the south and central areas, where pinch points were also mainly concentrated. Barriers were distributed on the edge of ecological sources and corridors. Based on ESP, the Daning river basin was divided into ecologically important areas in northern and eastern and ecologically improving areas in central and southern, the corresponding ecological restoration measures were also proposed. In summary, this study makes up for the shortcomings of constructing ESPs by the simple spatial overlaying of ecosystem services. Our findings could also effectively enhance the robustness and sustainability of ESPs in karst areas.